El acoso sexista callejero stalking, a la luz del Derecho Comparado - Pilacuán Pérez, Jéssica Valeria (2025)
The legal problem lies in the fact that, in many countries such as Ecuador, there is no clear and specific regulation to punish this type of violence, which generates a legal vacuum that prevents victims from accessing adequate protection, contributes to the impunity of the aggressors and perpetuates the normalization of this form of violence in public spaces. The general objective of this research was to analyze sexist street harassment, a form of gender violence. Gender violence refers to any act that results in, or is likely to result in, physical, sexual, or psychological harm or suffering to women, including threats of such acts, coercion, or arbitrary deprivation of liberty, whether occurring in public or in private life. This was done through a qualitative and comparative study to identify the feasibility and relevance of a possible specific legal regulation against street harassment. For this purpose, a qualitative approach methodology was used, using the comparative method, since the legislation of Colombia, Argentina, and Spain, where this conduct is regulated as an offense, was analyzed. With this analysis, it is determined that these different States specifically contemplate stalking as an autonomous crime in their legal systems, which facilitates its application and contributes to the reparation of the victims. In this sense, Ecuador could adopt a similar regulation to safeguard the legal assets of physical and moral integrity and human dignity to effectively guarantee the constitutional rights of the persons affected by this type of violence.